Design of bionic prosthetic leg - Aldiansyah Wahyu Pratama; Daryono Daryono; Mulyono Mulyono (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2022)
Along with the increase in the number of Indonesian people who are physically disabled and the number of cases of leg amputations above the knee, the need for prosthetic limbs in Indonesia is also increasing. Prosthetic limbs are tools to replace lost limbs caused by birth defects, amputations, or disease. The bionic prosthetic leg has a long-term useful purpose, as well as supporting the rights of people with disabilities. The device helps the above-the-knee amputee. To design a bionic prosthetic leg, a biomechanical analysis of work is needed to obtain a walking pattern in humans and an analysis of the structure and working material to obtain a safe and comfortable material for use in a bionic prosthetic foot. This bionic leg prosthetic uses an automatic system using an Electromyography (EMG) sensor as a signal picker for the muscles, Arduino Mega 2560 as an input signal processor which is then converted into an output signal and Planetary gear as a knee joint transmission so that the body does not fall forward or backward. The results of the analysis using Autodesk Inventor software on the prosthetic of the bionic leg can withstand a pressure of 404.526 MPa, withstand a reaction force of 354.576 N and a reaction moment of 15.4073 N. So based on the results of the bionic prosthetic leg is very safe and comfortable when used on people with disabilities.